Antimony-free flame-retardant polyvinyl chloride composite material and preparation method thereof
By adopting a synergistic flame retardant system of phosphorus-nitrogen-brominate and multi-system composite flame retardant technology, the environmental protection and economic problems of using antimony as a flame retardant additive in the prior art are solved, and the efficient flame retardant and good processing performance of antimony-free and environmentally friendly flame retardant polyvinyl chloride composite materials are achieved.
Patent Information
- Application Number
- CN202510181449.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-18
AI Technical Summary
In the prior art, in order to improve the flame retardancy of PVC composite materials, antimony trioxide is often used as flame retardant additives. However, due to the toxicity and cost of antimony and its compounds, environmental protection and economic problems have been caused, and it is difficult to achieve antimony-free and environmentally friendly flame retardant materials.
A synergistic flame retardant system of phosphorus-nitrogen-bromo is used to form a multi-system composite flame retardant technology by using hexaphenoxycyclotriphosphazene, 2,3-dibromosexualic anhydride, a nitrogen-based flame retardant, and a mixture of silicone resin and sodium silicate as a flame retardant, and combined with vinyl chloride-acrylate copolymer resin as a flow modifier to form a multi-system composite flame retardant technology.
The excellent flame retardant properties and good processing flowability of antimony-free flame retardant polyvinyl chloride composite materials are achieved, the amount of flame retardant is used, the mechanical properties and weather resistance of the material are improved, and the modern industry needs for safe and sustainable products are met.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyvinyl chloride composite materials and relates to an antimony-free flame-retardant polyvinyl chloride composite material and a preparation method thereof. Background Art
[0002] Polyvinyl chloride (PVC), as a common plastic material, is one of the most widely used plastics in the world. With its excellent insulation properties, corrosion resistance and mechanical strength, it occupies an important position in many fields such as construction, medical treatment, furniture and packaging. PVC material itself has flame retardant properties, is not easy to ignite in the air, and has excellent flame retardancy, which makes it an ideal choice for many applications. However, when it is necessary to prepare soft PVC, in order to achieve the required softness, a large amount of plasticizers such as phthalates, fatty acid esters and epoxies must be added. Although these plasticizers can improve the softness of PVC products, they also bring problems: on the one hand, they increase the fire risk of the material because the addition of plasticizers reduces the oxygen index of the composite material; on the other hand, some plasticizers may have adverse effects on the environment and human health.
[0003] At present, in order to improve the flame retardancy of PVC composite materials, antimony trioxide is usually used as the main flame retardant additive. This method is widely used in many patent technologies, such as CN116987356A, CN111269508A, CN104448613A and CN115772303A, all of which enhance the flame retardancy of materials by adding antimony trioxide. However, with the increase of environmental awareness and concern for health, the toxicity of antimony and its compounds has gradually attracted attention. Long-term contact or large-scale exposure to antimony elements may cause antimony poisoning, irritation of the skin and respiratory diseases, so major environmental protection organizations have begun to limit the antimony content in products, especially in flame retardant materials. In addition, due to the rising cost of antimony-based flame retardants, the overall cost of flame retardant materials has increased, which has further prompted the industry to find more environmentally friendly and economical alternatives.
[0004] In response to the above challenges, the development of antimony-free, environmentally friendly, flame-retardant PVC composite materials has become a technical problem that urgently needs to be solved. Metal hydroxides, such as aluminum hydroxide and magnesium hydroxide, have been considered as antimony-free flame retardants, as shown in Chinese patent CN105837998A, which introduces a PVC sheath material using these two substances as flame retardants. Although this method achieves antimony-free, due to the relatively weak effect of such flame retardants, it is often necessary to significantly increase the filling amount to achieve the ideal flame retardant effect, which in turn leads to a decrease in the mechanical properties of the material, thereby limiting its scope of application.
[0005] The Chinese patent application document (publication number: CN101942156A) discloses a highly flame-retardant polyvinyl chloride cable material and its preparation method, and uses antimony trioxide, hydroxide, phosphorus-nitrogen composite zinc borate as a compound flame retardant to prepare a highly flame-retardant polyvinyl chloride composite material. The material achieves an ideal flame retardant effect, but does not achieve antimony-free flame retardancy.
[0006] The Chinese patent application document (publication number: CN101914217A) discloses an environmentally friendly flame retardant that replaces antimony trioxide. The flame retardant can replace antimony trioxide in equal amounts in PVC, polyolefin plastics, engineering plastics, rubber and unsaturated resins. Although it has achieved the replacement of antimony trioxide and improved the cost performance of the material, it is only a partial replacement and does not completely solve the problem of antimony-free.
[0007] A Chinese patent application document (publication number: CN104403224A) discloses an antimony-free flame-retardant polyvinyl chloride cable material and a preparation method thereof. The invention uses traditional filler-type inorganic substances such as hydroxides, montmorillonite, and kaolin as flame retardants. The flame retardant mechanism is simple, and due to the large amount of inorganic incompatible ingredients added, the efficacy of each component in the formula system cannot be fully exerted, resulting in poor overall performance of the final material, especially its poor flow processing performance, which greatly affects the scope of use of the material. Summary of the invention
[0008] The purpose of the present invention is to solve the above problems in the prior art and to provide an antimony-free flame-retardant polyvinyl chloride composite material with excellent flame retardant properties and processable fluidity.
[0009] The purpose of the present invention can be achieved by the following technical solutions: An antimony-free flame-retardant polyvinyl chloride composite material comprises the following raw materials in parts by weight: 50-150 parts of polyvinyl chloride, 1-10 parts of a stabilizer, 30-60 parts of a plasticizer, 5-30 parts of hexaphenoxy cyclotriphosphazene, 5-20 parts of 2,3-dibromosuccinic anhydride, 5-25 parts of a nitrogen-based flame retardant, 1-15 parts of a flame retardant synergist, 0.1-5 parts of a lubricant, 10-25 parts of a flow modifier, 0.1-5 parts of an antioxidant, 0.1-1.5 parts of an anti-ultraviolet absorber, and 1-20 parts of a filler.
[0010] Preferably, the composite material comprises the following raw materials in parts by weight: 80-120 parts of polyvinyl chloride, 4-6 parts of stabilizer, 40-50 parts of plasticizer, 15-20 parts of hexaphenoxy cyclotriphosphazene, 8-12 parts of 2,3-dibromosuccinic anhydride, 8-12 parts of nitrogen flame retardant, 3-10 parts of flame retardant synergist, 0.5-1 parts of lubricant, 10-15 parts of flow modifier, 0.4-0.6 parts of antioxidant, 0.4-0.6 parts of anti-ultraviolet absorber, and 5-15 parts of filler.
[0011] Preferably, the average polymerization degree of polyvinyl chloride is 700-1600.
[0012] In the above-mentioned antimony-free flame-retardant polyvinyl chloride composite material, the stabilizer is at least one of epoxy fatty acid calcium zinc, glycerol zinc, calcium stearate, zinc stearate, dimer acid calcium zinc, and amino acid zinc. The stabilizer is used to delay the thermal decomposition process of PVC and prevent it from being thermally decomposed due to high temperature during processing.
[0013] In the above-mentioned antimony-free flame-retardant polyvinyl chloride composite material, the plasticizer is at least one of dioctyl terephthalate, dioctyl adipate, epoxy soybean oil, and trioctyl trimellitate. By adding the plasticizer, the present invention can improve the softness of PVC, reduce the crystallinity of the PVC molecular chain, increase its plasticity, and make it easier to plasticize and process.
[0014] In the above-mentioned antimony-free flame-retardant polyvinyl chloride composite material, the nitrogen-based flame retardant is at least one of melamine cyanurate, melamine polyphosphate and melamine phosphate.
[0015] In the above antimony-free flame-retardant polyvinyl chloride composite material, the flame retardant synergist is a mixture of organic silicone resin and sodium silicate.
[0016] Preferably, the flame retardant synergist is a mixture of silicone resin and sodium silicate in a mass ratio of (1-5):1.
[0017] More preferably, the flame retardant synergist is a mixture of silicone resin and sodium silicate in a mass ratio of (2-3):1.
[0018] The flame retardant used in the present invention is a composite flame retardant with hexaphenoxy cyclotriphosphazene, 2,3-dibromosuccinic anhydride, and nitrogen-based flame retardant as the main flame retardant, and a mixture formed by silicone resin and sodium silicate as a flame retardant synergist. Hexaphenoxy cyclotriphosphazene has a six-membered ring structure composed of alternating single and double bonds of phosphorus and nitrogen atoms, has high thermal stability, decomposes under high temperature to produce polyphosphoric acid and partial polyphosphoric acid, and covers the surface of the carbon layer, playing a condensed phase flame retardant role; at the same time, the combustion process also produces phosphorus oxygen free radicals and flame retardant gases, which can terminate the free radical chain reaction and dilute the concentration of combustible gas, slow down the further combustion of PVC, and show a gas phase flame retardant effect. 2,3-Dibromosuccinic anhydride is a reactive flame retardant, and its molecular structure contains bromine elements, which enables it to capture free radicals in the combustion reaction during the combustion process, such as HO·, H·, ·O·, etc., thereby cutting off the combustion chain reaction, inhibiting the free radical chain reaction, and reducing the combustion speed until the flame is extinguished. The flame retardant mechanism of nitrogen-based flame retardants is mainly to improve the flame retardancy of materials by releasing nitrogen, inhibiting free radical chain reactions, increasing the carbon deposition layer during combustion to reduce the combustion performance of combustible materials, and other methods. The present invention forms a phosphorus-nitrogen-bromine synergistic flame retardant system through hexaphenoxy cyclotriphosphazene, 2,3-dibromosuccinic anhydride, and nitrogen-based flame retardants. Phosphorus, nitrogen, and bromine elements each play different roles in the combustion process to form a synergistic effect. Hexaphenoxy cyclotriphosphazene forms a carbon layer, nitrogen-based flame retardants release non-flammable gases, and 2,3-dibromosuccinic anhydride interrupts the combustion chain reaction. The synergistic effect of the three can better isolate heat transfer and improve flame retardant efficiency. Silicone resin and sodium silicate are then added as flame retardant synergists to enhance the carbonization effect and further improve flame retardant performance. The synergistic effect of multi-system flame retardancy improves the flame retardant efficiency of polymers and reduces the amount of certain flame retardants in the flame retardant system. Under the premise of meeting high flame retardant requirements, the cost can be well controlled, and low-amount and high-efficiency flame retardants are also achieved.
[0019] In the above-mentioned antimony-free flame-retardant polyvinyl chloride composite material, the lubricant is at least one of ethylene bis stearamide, oxidized polyethylene wax, and stearic acid glycerol. The lubricant used in the present invention, on the one hand, increases the lubrication performance of the composite material and the metal processing equipment, and prevents the polyvinyl chloride composite material from adhering to the processing equipment; on the other hand, after being melted, it melts into the interior of the PVC melt, plays a role of lubrication between molecules in the melt, appropriately reduces internal friction, improves flowability, and facilitates processing and molding.
[0020] In the above-mentioned antimony-free flame-retardant polyvinyl chloride composite material, the flow modifier is vinyl chloride-acrylate copolymer resin.
[0021] Preferably, the vinyl chloride-acrylate copolymer resin has an intrinsic viscosity of 5-30 ml / g and contains 3-8% by mass of acrylate monomer.
[0022] More preferably, the acrylate monomer is at least one of n-butyl acrylate and ethyl acrylate.
[0023] Vinyl chloride-acrylate copolymer resin is a copolymerized polymer compound with vinyl chloride as the main body and acrylate monomers introduced into the copolymer. The copolymer contains polyvinyl chloride structural units and has excellent compatibility and blending properties with polyvinyl chloride resin; the polar acrylate groups it contains can achieve molecular compatibility with other inorganic additives in the composite material. The addition of this substance enables the various components in the composite material to achieve perfect blending compatibility, which not only improves the flow processing performance of the composite material, but also enables the efficacy of each component to be fully exerted and the compatibility of each component to be more reasonable and efficient. Vinyl chloride-acrylate copolymer resin also has a plasticizing effect on PVC, reduces the amount of plasticizer in the composite material, reduces the impact of plasticizers on flame retardant properties and the surface migration of plasticizers after a long time. At the same time, vinyl chloride-acrylate copolymer resin can also significantly improve the low-temperature flexibility and impact strength of PVC products, and can also improve the surface gloss and delicate texture of PVC products. In the production process, it can reduce the melt viscosity, improve the flow performance, shorten the plasticizing time, and increase the unit output.
[0024] In order to prevent and alleviate the degradation and aging of PVC during processing and use and improve the overall quality of PVC products, the present invention adds antioxidants and anti-ultraviolet absorbers to the formula system to improve the light resistance and weather resistance of the polyvinyl chloride composite material.
[0025] Preferably, the antioxidant is at least one of a phenolic antioxidant, a thiol antioxidant, a phosphite, and a pentaerythritol ester antioxidant. The present invention does not make any special requirements on the specific selection of the antioxidant, and any phenolic antioxidant, thiol antioxidant, amide antioxidant, and pentaerythritol ester antioxidant that can play an antioxidant role is within the protection scope of the present invention. As an example, phenolic antioxidants include one or more of butylated hydroxytoluene, butylated hydroxyanisole, tert-butylhydroquinone, and antioxidant 1076; thiol antioxidants include one or more of tetrapropionic acid disulfide, lipoic acid, acetylcysteine, cysteine, and glutathione; phosphite antioxidants include one or more of tris(2,4-di-tert-butylphenol)phosphite, dioctadecyl pentaerythritol diphosphite, and bis(3,5-di-tert-butylphenol)pentaerythritol diphosphite; pentaerythritol ester antioxidants include one or more of pentaerythritol diphosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and pentaerythritol tetrakis(3-laurylthiopropionate).
[0026] Preferably, the anti-ultraviolet absorber can be selected from at least one of benzotriazole anti-ultraviolet absorbers, hindered amine anti-ultraviolet absorbers, and benzophenone anti-ultraviolet absorbers. The present invention does not make special requirements for the selection of anti-ultraviolet absorbers. Any benzotriazole anti-ultraviolet absorbers, hindered amine anti-ultraviolet absorbers, and benzophenone anti-ultraviolet absorbers that can play an anti-ultraviolet role are within the protection scope of the present invention. Benzotriazole anti-ultraviolet absorbers may include one or more of 2-(2-hydroxy 3,5-di-tert-butyl)-5-chloro-benzotriazole, 2-(2-hydroxy 5-methyl-benzotriazole, and 2-(2-hydroxy-3-tert-butyl-5-methyl)-5-chloro-benzotriazole; hindered amine anti-ultraviolet absorbers can be selected from bis-1,2,2,6,6-pentamethylpiperidinol sebate, bis-1-octyloxy-2,2,6,6-tetradecanoate. One or more of methyl piperidine alcohol ester, poly 1-octyloxy-2,2,6,6-tetramethyl piperidine alcohol sebacate, and poly succinic acid (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) ester; the benzophenone anti-ultraviolet absorber can be listed as one or more of 2-hydroxy-4-n-octyloxy benzophenone (ultraviolet absorber UV-531), ultraviolet absorber UV-9, and ultraviolet absorber UV-284.
[0027] In the above-mentioned antimony-free flame-retardant polyvinyl chloride composite material, the filler is a mixture of calcium silicate and graphene.
[0028] Preferably, the filler is a mixture of calcium silicate and graphene in a mass ratio of (1-1.5):(1.5-2.5).
[0029] More preferably, the average particle size of the filler is 1-2 um.
[0030] The filler of the present invention uses a unique mixture of calcium silicate and graphene, and the mass ratio is preferably 1-1.5:1.5-2.5. Furthermore, in order to ensure optimal performance, the average particle size of this filler is strictly controlled between 1-2 um. It cleverly combines the advantages of calcium silicate and graphene, among which calcium silicate can not only significantly improve the hardness, strength and wear resistance of the composite material, but also effectively reduce costs and improve the processing performance and fluidity of the material. Graphene, as one of the hardest and strongest materials known, has an ultra-high specific surface area, and even a very small amount of addition can greatly improve the mechanical strength and other mechanical properties of the composite material. By mixing these two components, not only can the dispersion and stability of graphene in the PVC matrix be optimized, ensuring the consistency and uniformity of the internal structure of the composite material, but also the mechanical properties of the material can be further enhanced, thereby developing a new antimony-free flame-retardant PVC composite material with high strength, good processability and cost-effectiveness.
[0031] The present invention also provides a method for preparing the above-mentioned antimony-free flame-retardant polyvinyl chloride composite material, the method comprising the following steps: S1, prepare the above raw materials; S2, firstly uniformly mixing hexaphenoxy cyclotriphosphazene, 2,3-dibromosuccinic anhydride, nitrogen flame retardant, flame retardant synergist and lubricant to obtain a flame retardant composite; S3, uniformly mixing the flame retardant compound and polyvinyl chloride, stabilizer, plasticizer, antioxidant, and anti-ultraviolet absorber, then adding the remaining raw materials and continuing to mix, then stirring and cold mixing, and discharging to obtain a semi-finished product; S4, adding the semi-finished product into an extruder, melting and extruding, and then granulating to obtain a finished composite material.
[0032] In the above-mentioned method for preparing an antimony-free flame-retardant polyvinyl chloride composite material, in step S3, the flame-retardant composite material and polyvinyl chloride, stabilizer, plasticizer, antioxidant, and anti-ultraviolet absorber are uniformly mixed until the temperature reaches 100-120° C., and then the remaining raw materials are added and mixed for 3-5 minutes.
[0033] The present invention mixes the flame retardant compound with polyvinyl chloride, stabilizer, plasticizer, antioxidant and anti-ultraviolet absorber as the first batch of materials. In the continuous high-speed mixing process, on the one hand, due to the collision and friction between the materials and between the materials and the mixer, the materials will be evenly dispersed in the entire formula system without agglomeration and "island" situation, so that each component in the final composite material can give full play to its own optimal performance, ensuring the quality consistency of the final product; on the other hand, in the mixing process, due to frictional heat generation, especially the friction between the flame retardant compound and other materials and equipment, the temperature of the material will continue to rise. During the heating process, the PVC resin particles wetted by the plasticizer gradually begin to swell from the surface to the inside, and the plasticizer is also continuously adsorbed into the inside of the PVC resin particles until the temperature reaches 100-120°C, and the PVC resin particles complete the adsorption of the plasticizer. The PVC resin adsorbed with the plasticizer can not only reduce the plasticizing time required in the subsequent processing process, improve its plasticity and thus improve production efficiency in the subsequent melt extrusion granulation process, but also reduce the melt viscosity to ensure the processing stability of the entire composite material and the various properties of the final composite material. Stabilizers, antioxidants and anti-UV absorbers can reduce the risk of high-temperature decomposition of PVC resin during high-temperature mixing of materials.
[0034] When the temperature of the first batch of materials reaches 100-120℃, add the remaining raw materials and continue mixing for 3-5 minutes. The flow modifier and filler are added later to prevent them from affecting the absorption of plasticizers by PVC resin particles, thereby ensuring that the PVC resin completely absorbs and swells the plasticizer during the mixing process. Continue mixing for 3-5 minutes to make the components more evenly mixed, to ensure that the materials can form a uniform melt state during subsequent extruder processing, reduce possible defects or unevenness problems, and ensure the quality and appearance of the extruded products.
[0035] In the above-mentioned method for preparing an antimony-free flame-retardant polyvinyl chloride composite material, the stirring and cold mixing time in step S3 is 10-30 minutes, and the discharge temperature is 20-40°C.
[0036] Preferably, the cold mixing temperature is 0-30°C.
[0037] The present invention can ensure that the material is further dispersed evenly while cooling by setting an appropriate stirring and cold mixing time (10-30 minutes), so that the material can still maintain a good particle shape and uniform dispersion effect before entering the subsequent high-temperature melt extrusion process, thereby ensuring smooth operation and high-quality output during the extrusion molding process; at the same time, it avoids the risk of material structure damage or performance degradation due to excessive mixing. Secondly, the discharge temperature is controlled within the range of 20-40°C, which effectively prevents the pre-plasticization of the material during the processing process. If the material is in a high temperature state for a long time during the mixing or storage stage, it will partially melt or soften in advance, that is, pre-plasticization. In this case, when the material enters the subsequent extruder, its melting behavior will be affected, resulting in problems such as excessive melt viscosity and poor fluidity, which in turn affects the quality of the final product, such as increased surface roughness and reduced dimensional accuracy. Rapid cooling during stirring and cold mixing can quickly take away the heat generated when the material is mixed, and keep the physical state of the material stable. This not only helps prevent the material from entering the plasticized state prematurely, but also reduces the molecular chain degradation or other adverse chemical reactions caused by thermal stress, ensuring the controllability of the overall performance of the subsequent composite material.
[0038] In the above-mentioned method for preparing an antimony-free flame-retardant polyvinyl chloride composite material, extrusion granulation is carried out in a twin-screw extruder, wherein the temperature of the feeding section of the twin-screw extruder is 120-140°C, the temperature of the melt plasticization section is 135-160°C, the temperature of the melt extrusion section is 135-150°C, and the temperature of the die section is 120-155°C; the main engine speed is 20-25rpm, and the feeding speed is 15-18rpm.
[0039] Preferably, the main properties of the antimony-free flame-retardant polyvinyl chloride composite material of the present invention are as follows: Tensile strength is 24~26Mpa, test standard: GB / T16421-1996; Oxygen index is 32-33%, test standard: GB / T5454-1997; Shore A hardness is 92-94, test standard: GB / T2411-2008; Color fastness grade reaches 5 and above, test standard: GB / T8427-2008; The melt index is 5-8 g / min, the test temperature is 190°C, the die is 2.095 mm, and the load is 2.16 kg.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] 1. The polyvinyl chloride composite material of the present invention does not contain antimony elements, but still maintains excellent flame retardant properties and good processing fluidity. By adopting a unique phosphorus-nitrogen-bromine synergistic flame retardant system to replace the traditional halogen-antimony flame retardant system, the goal of antimony-free flame retardancy is successfully achieved, and the technical problem of the negative impact of inorganic flame retardant modification on the mechanical properties and fluidity of polyvinyl chloride materials is solved. This environmentally friendly flame-retardant PVC composite material can not only meet the needs of modern industry for safe and sustainable products, but also enhances the bonding force between each component and the PVC matrix due to its uniform dispersion between components and the use of special modifiers, thereby ensuring the overall performance of the material.
[0042] 2. The PVC composite material of the present invention exhibits excellent mechanical properties and abrasion resistance, which makes it more stable and reliable in the face of physical stress in daily use. Whether used as a building material or an industrial product, this material can provide a durable solution and reduce the frequency of product failure or replacement due to wear and tear.
[0043] 3. The PVC composite material of the present invention has excellent weather resistance and can effectively resist the effects of sunlight, ultraviolet radiation and extreme temperature changes. This means that even if exposed to outdoor environments for a long time, the material is not easy to age or deteriorate and maintains its original physical and chemical properties. This is particularly important for applications that require long-term stability and reliability.
[0044] 4. The method for preparing the PVC composite material provided by the present invention is simple and easy to operate, has low manufacturing cost and high production efficiency, and is very suitable for large-scale industrial production. It provides manufacturers with a solution that can both ensure product quality and achieve economic benefits, and helps to promote the entire industry to develop in a more environmentally friendly and efficient direction. In short, this invention represents a major advancement in the field of PVC composite materials, bringing a new option that is both safe and economical to the market. DETAILED DESCRIPTION
[0045] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments. Example 1
[0046] S1. Prepare the raw materials according to the following mass parts: 100 parts of polyvinyl chloride, 4 parts of stabilizer, 45 parts of plasticizer, 20 parts of hexaphenoxy cyclotriphosphazene, 12 parts of 2,3-dibromosuccinic anhydride, 10 parts of nitrogen flame retardant, 8 parts of flame retardant synergist, 0.5 parts of lubricant, 0.5 parts of antioxidant, 0.5 parts of anti-ultraviolet absorber, 12 parts of filler, and 13 parts of flow modifier; The stabilizer is a mixture of calcium stearate and zinc stearate in a mass ratio of 1:1; The plasticizer is a mixture of dioctyl terephthalate, dioctyl adipate, and epoxidized soybean oil in a mass ratio of 4:1:1; The nitrogen flame retardant is a mixture of melamine polyphosphate and melamine phosphate in a mass ratio of 1:1; The flame retardant synergist is a mixture of silicone resin and sodium silicate in a mass ratio of 2.5:1. The silicone resin was purchased from Shin-Etsu Chemical Co., Ltd., Japan, model KR-220LP; The lubricant is oxidized polyethylene wax; The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate; The anti-ultraviolet absorber is 2-(2-hydroxy-3-tert-butyl-5-methyl)-5-chloro-benzotriazole; The filler is a mixture of calcium silicate and graphene in a mass ratio of 1.2:2, with an average particle size of 1.5um; The flow modifier is a vinyl chloride-acrylate copolymer resin with an intrinsic viscosity of 20 ml / g and a mass fraction of n-butyl acrylate monomer of 7%.
[0047] S2, firstly stirring hexaphenoxy cyclotriphosphazene, 2,3-dibromosuccinic anhydride, nitrogen flame retardant, flame retardant synergist, and lubricant to obtain a flame retardant composite;
[0048] S3. Mix the flame retardant compound, polyvinyl chloride, stabilizer, plasticizer, antioxidant and anti-ultraviolet absorber in a mixer to 115°C, then add the remaining raw materials and continue mixing for 5 minutes. Then, stir and cold mix the materials at 20°C for 25 minutes, cool to about 30°C and then discharge to obtain a semi-finished product for standby use.
[0049] S4, adding the semi-finished product material after mixing and cooling into a parallel twin-screw extruder, melting and extruding, and then granulating to obtain a finished composite material.
[0050] The temperatures of each section of the parallel twin-screw extruder during granulation are as follows: feeding section 135°C, melt plasticization section 145°C, melt extrusion section 150°C, die section 148°C. The main engine speed is 23rpm, and the feeding speed is 16rpm. Example 2
[0051] The only difference from Example 1 is that the raw materials are configured according to the following mass parts: 100 parts of polyvinyl chloride, 4 parts of stabilizer, 45 parts of plasticizer, 18 parts of hexaphenoxy cyclotriphosphazene, 10 parts of 2,3-dibromosuccinic anhydride, 9 parts of nitrogen-based flame retardant, 5 parts of flame retardant synergist, 0.5 parts of lubricant, 0.5 parts of antioxidant, 0.5 parts of anti-ultraviolet absorber, 12 parts of filler, and 13 parts of flow modifier. Example 3
[0052] The only difference from Example 1 is that the raw materials are configured according to the following mass parts: 100 parts of polyvinyl chloride, 4 parts of stabilizer, 45 parts of plasticizer, 15 parts of hexaphenoxy cyclotriphosphazene, 8 parts of 2,3-dibromosuccinic anhydride, 8 parts of nitrogen-based flame retardant, 3 parts of flame retardant synergist, 0.5 parts of lubricant, 0.5 parts of antioxidant, 0.5 parts of anti-ultraviolet absorber, 12 parts of filler, and 13 parts of flow modifier. Example 4
[0053] The only difference from Example 1 is that the raw materials are prepared according to the following mass parts: 100 parts of polyvinyl chloride, 4 parts of stabilizer, 45 parts of plasticizer, 20 parts of hexaphenoxy cyclotriphosphazene, 12 parts of 2,3-dibromosuccinic anhydride, 10 parts of nitrogen flame retardant, 8 parts of flame retardant synergist, 0.5 parts of lubricant, 0.5 parts of antioxidant, 0.5 parts of anti-ultraviolet absorber, 8 parts of filler, and 13 parts of flow modifier; The plasticizer is a mixture of dioctyl terephthalate, trioctyl trimellitate and epoxy soybean oil in a mass ratio of 4:1:1; the nitrogen flame retardant is a mixture of melamine cyanurate and melamine polyphosphate in a mass ratio of 1:1. Example 5
[0054] The only difference from Example 1 is that the raw materials are prepared according to the following mass parts: 100 parts of polyvinyl chloride, 4 parts of stabilizer, 45 parts of plasticizer, 20 parts of hexaphenoxy cyclotriphosphazene, 12 parts of 2,3-dibromosuccinic anhydride, 10 parts of nitrogen flame retardant, 8 parts of flame retardant synergist, 0.5 parts of lubricant, 0.5 parts of antioxidant, 0.5 parts of anti-ultraviolet absorber, 15 parts of filler, and 13 parts of flow modifier; The plasticizer is a mixture of dioctyl terephthalate, trioctyl trimellitate and epoxy soybean oil in a mass ratio of 4:1:1; the nitrogen flame retardant is a mixture of melamine cyanurate and melamine polyphosphate in a mass ratio of 1:1. Example 6
[0055] The only difference from Example 1 is that the raw materials are configured according to the following mass parts: 100 parts of polyvinyl chloride, 4 parts of stabilizer, 45 parts of plasticizer, 20 parts of hexaphenoxy cyclotriphosphazene, 12 parts of 2,3-dibromosuccinic anhydride, 10 parts of nitrogen-based flame retardant, 8 parts of flame retardant synergist, 0.5 parts of lubricant, 0.5 parts of antioxidant, 0.5 parts of anti-ultraviolet absorber, 12 parts of filler, and 10 parts of flow modifier. Example 7
[0056] The only difference from Example 1 is that the raw materials are configured according to the following mass parts: 100 parts of polyvinyl chloride, 4 parts of stabilizer, 45 parts of plasticizer, 20 parts of hexaphenoxy cyclotriphosphazene, 12 parts of 2,3-dibromosuccinic anhydride, 10 parts of nitrogen-based flame retardant, 8 parts of flame retardant synergist, 0.5 parts of lubricant, 0.5 parts of antioxidant, 0.5 parts of anti-ultraviolet absorber, 12 parts of filler, and 15 parts of flow modifier. Example 8
[0057] The only difference from Example 1 is that the raw materials are prepared according to the following mass parts: 100 parts of polyvinyl chloride, 4 parts of stabilizer, 45 parts of plasticizer, 20 parts of hexaphenoxy cyclotriphosphazene, 12 parts of 2,3-dibromosuccinic anhydride, 10 parts of nitrogen flame retardant, 8 parts of flame retardant synergist, 0.5 parts of lubricant, 0.5 parts of antioxidant, 0.5 parts of anti-ultraviolet absorber, 12 parts of filler, and 13 parts of flow modifier; Among them, the plasticizer is a mixture of trioctyl trimellitate, dioctyl adipate and epoxy soybean oil in a mass ratio of 4:1:1; the nitrogen flame retardant is a mixture of melamine cyanurate, melamine polyphosphate and melamine phosphate in a mass ratio of 1:1:1; the flame retardant synergist is a mixture of silicone resin and sodium silicate in a mass ratio of 2:1; the flow modifier is a vinyl chloride-acrylate copolymer resin with a characteristic viscosity of 20 ml / g and a mass fraction of ethyl acrylate monomer of 7%; and the antioxidant is dioctadecyl alcohol pentaerythritol diphosphite. Comparative Example 1
[0058] The only difference from Example 1 is that the raw material of Comparative Example 1 does not contain 2,3-dibromosuccinic acid, and the amount of hexaphenoxytriphosphazene is 32 parts. Comparative Example 2
[0059] The only difference from Example 1 is that the amount of 2,3-dibromosuccinic acid added to the raw material of Comparative Example 2 is 3 parts. Comparative Example 3
[0060] The only difference from Example 1 is that the raw materials of Comparative Example 3 do not contain nitrogen-based flame retardant, wherein the amount of hexaphenoxytriphosphazene is 30 parts. Comparative Example 4
[0061] The only difference from Example 1 is that the raw materials of Comparative Example 4 do not contain a flame retardant synergist, wherein the amount of hexaphenoxytriphosphazene is 28 parts. Comparative Example 5
[0062] The only difference from Example 1 is that the flame retardant synergist in the raw material of Comparative Example 5 is only sodium silicate. Comparative Example 6
[0063] The only difference from Example 1 is that the flame retardant synergist in the raw materials of Comparative Example 6 is only silicone resin. Comparative Example 7
[0064] The only difference from Example 1 is that the raw materials are configured according to the following mass parts: 100 parts of polyvinyl chloride, 4 parts of stabilizer, 45 parts of plasticizer, 10 parts of hexaphenoxy cyclotriphosphazene, 7 parts of 2,3-dibromosuccinic anhydride, 6 parts of nitrogen-based flame retardant, 2 parts of flame retardant synergist, 0.5 parts of lubricant, 0.5 parts of antioxidant, 0.5 parts of anti-ultraviolet absorber, 12 parts of filler, and 13 parts of flow modifier. Comparative Example 8
[0065] The only difference from Example 1 is that the raw materials of Comparative Example 8 do not contain fillers. Comparative Example 9
[0066] The only difference from Example 1 is that the filler in the raw material of Comparative Example 9 is only calcium silicate. Comparative Example 10
[0067] The only difference from Example 1 is that the filler in the raw material of Comparative Example 10 is only graphene. Comparative Example 11
[0068] The only difference from Example 1 is that the filler in the raw material of Comparative Example 11 is a mixture of calcium carbonate and graphene in a mass ratio of 1.2:2. Comparative Example 12
[0069] The only difference from Example 1 is that the raw material of Comparative Example 12 does not contain a flow modifier. Comparative Example 13
[0070] The only difference from Example 1 is that the amount of flow modifier added to the raw material of Comparative Example 13 is 5 parts. Comparative Example 14
[0071] The only difference from Example 1 is that the content of n-butyl acrylate in the flow modifier in the raw material of Comparative Example 14 is 1.5%. Comparative Example 15
[0072] The only difference from Example 1 is that the intrinsic viscosity of the flow improver in the raw material of Comparative Example 15 is 40.
[0073] The polyvinyl chloride composite materials of Examples 1-8 and Comparative Examples 1-15 were tested for physical and chemical properties, and the test labels are as follows: oxygen index test standard GB / T5454-1997; light fastness test standard GB / T8427-2008; tensile strength test standard GB / T16421-1996; Shore A hardness test standard: GB / T2411-2008; melt index test temperature 190°C, die 2.095mm, load 2.16Kg. The test results are shown in Table 1: Table 1: Physical and chemical properties of polypropylene composite materials prepared in Examples 1-8 and Comparative Examples 1-15
[0074] As can be seen from Table 1, the antimony-free flame-retardant polyvinyl chloride composite material prepared by the present invention has excellent mechanical properties, processing flow properties and weather resistance, and has excellent flame retardant properties.
[0075] The polyvinyl chloride composite material formula system of the present invention adopts a multi-system composite flame retardant technology, fully utilizing the multi-mechanism synergistic effect between the flame retardants, and with the cooperation of the flow modifier, the flame retardant effect is well exerted. Within a certain range, as the flame retardant component in the system increases, the flame retardant performance of the composite material is improved, as shown in Examples 1, 2, and 3.
[0076] The reactive flame retardant 2,3-dibromosuccinic anhydride plays a good role in inhibiting free radical chain reactions and preventing combustion in the system. When it is not added or the amount added is too small, it has a great effect on the flame retardancy of the composite material, see Example 1 and Comparative Examples 1-2. Nitrogen-based flame retardants and flame retardant synergists play a very obvious synergistic role in the flame retardant properties of the composite material of the present invention. When nitrogen-based flame retardants or flame retardant synergists are not added, or when the organic silicon component and sodium silicate component in the flame retardant synergist are missing, it not only affects the flame retardant properties of the material, but also affects the mechanical properties and processing fluidity of the material, see Example 1 and Comparative Examples 3-6. When the amount of flame retardant components added in the formula system is too small, the flame retardant properties of the composite material are significantly reduced, see Example 1 and Comparative Example 7.
[0077] The present invention uses a mixture of ultrafine calcium silicate and graphene as a filler, so that the mechanical properties of the composite material are significantly improved; within a certain range, as the filler component increases, the mechanical properties of the obtained material are also increased, see Examples 4 and 5. The filler of the present invention is a compound system. If the filler is not added to the formula system, or the filler does not contain graphene and calcium silicate components, it will directly affect the mechanical properties of the final material, see Example 1 and Comparative Examples 8, 9, and 11. If the filler in the formula system is all graphene, the dispersion and compatibility effects of the system are affected due to the excessive addition of graphene, so that the various properties of the final composite material are significantly reduced, see Example 1 and Comparative Example 10.
[0078] It can also be seen from the above table that the composite material of the present invention adopts vinyl chloride-acrylate copolymer resin as flow modifier, which can not only improve the compatibility of each component in the formula, but also improve the processability fluidity and mechanical properties of the material. When vinyl chloride-acrylate copolymer resin is not added or its addition amount is reduced, the mechanical properties, flame retardancy, and flow processing properties of the material will be reduced, see Examples 1, 6, 7 and Comparative Examples 12, 13. In addition, the acrylate monomer content and intrinsic viscosity in the vinyl chloride-acrylate copolymer resin have an impact on the processability fluidity and other comprehensive properties of the final composite material. If the acrylate monomer content is low or the intrinsic viscosity is too high, the compatibility effect provided by it to the system is poor, and the compatibility of each component is imperfect, resulting in a decrease in the various properties of the final material, see Example 1 and Comparative Examples 14, 15.
[0079] The parts of the embodiments herein that are not exhaustive of the midpoint values of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.
[0080] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.
[0081] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. An antimony-free flame-retardant polyvinyl chloride composite material, characterized in that: The composite material comprises the following raw materials in parts by weight: 50-150 parts of polyvinyl chloride, 1-10 parts of a stabilizer, 30-60 parts of a plasticizer, 5-30 parts of hexaphenoxy cyclotriphosphazene, 5-20 parts of 2,3-dibromosuccinic anhydride, 5-25 parts of a nitrogen-based flame retardant, 1-15 parts of a flame retardant synergist, 0.1-5 parts of a lubricant, 10-25 parts of a flow modifier, 0.1-5 parts of an antioxidant, 0.1-1.5 parts of an anti-ultraviolet absorber, and 1-20 parts of a filler.
2. The antimony-free flame-retardant polyvinyl chloride composite material according to claim 1, characterized in that: The stabilizer is at least one of epoxy fatty acid calcium zinc, glycerol zinc, calcium stearate, zinc stearate, dimer acid calcium zinc, and amino acid zinc; And / or the plasticizer is at least one of dioctyl terephthalate, dioctyl adipate, epoxidized soybean oil, and trioctyl trimellitate.
3. The antimony-free flame-retardant polyvinyl chloride composite material according to claim 1, characterized in that: The nitrogen-based flame retardant is at least one of melamine cyanurate, melamine polyphosphate, and melamine phosphate.
4. The antimony-free flame-retardant polyvinyl chloride composite material according to claim 1, characterized in that: The flame retardant synergist is a mixture of an organic silicone resin and sodium silicate, and / or the flame retardant synergist is a mixture of an organic silicone resin and sodium silicate in a mass ratio of (1-5):
1.
5. The antimony-free flame-retardant polyvinyl chloride composite material according to claim 1, characterized in that: The flow modifier is a vinyl chloride-acrylate copolymer resin, wherein the vinyl chloride-acrylate copolymer resin has an intrinsic viscosity of 5-30 ml / g and contains 3-8% by mass of an acrylate monomer; and / or the lubricant is at least one of ethylene bisstearamide, oxidized polyethylene wax, and glyceryl stearate; and / or the antioxidant is at least one of a phenolic antioxidant, a thiol antioxidant, a phosphite antioxidant, and a pentaerythritol ester antioxidant; And / or the anti-ultraviolet absorber is at least one of a benzotriazole anti-ultraviolet absorber, a hindered amine anti-ultraviolet absorber, and a benzophenone anti-ultraviolet absorber.
6. The antimony-free flame-retardant polyvinyl chloride composite material according to claim 1, characterized in that: The filler is a mixture of calcium silicate and graphene; And / or the average particle size of the filler is 1-2 um.
7. A method for preparing the antimony-free flame-retardant polyvinyl chloride composite material according to claim 1, characterized in that: The method comprises the following steps: S1. Prepare the raw materials according to claim 1; S2, firstly uniformly mix hexaphenoxy cyclotriphosphazene, 2,3-dibromosuccinic anhydride, nitrogen flame retardant, flame retardant synergist and lubricant to obtain a flame retardant composite; S3, uniformly mixing the flame retardant compound and polyvinyl chloride, stabilizer, plasticizer, antioxidant, and anti-ultraviolet absorber, then adding the remaining raw materials and continuing to mix, then stirring and cold mixing, and discharging to obtain a semi-finished product; S4, adding the semi-finished product into an extruder, melting and extruding, and then granulating to obtain a finished composite material.
8. The method for preparing an antimony-free flame-retardant polyvinyl chloride composite material according to claim 7, characterized in that: Step S3: After the flame retardant compound and polyvinyl chloride, stabilizer, plasticizer, antioxidant and anti-ultraviolet absorber are uniformly mixed and the temperature reaches 100-120° C., the remaining raw materials are added and mixed for 3-5 minutes.
9. The method for preparing an antimony-free flame-retardant polyvinyl chloride composite material according to claim 7, characterized in that: The stirring and cold mixing time in step S3 is 10-30 minutes, and the discharge temperature is 20-40°C.
10. The method for preparing an antimony-free flame-retardant polyvinyl chloride composite material according to claim 7, characterized in that: Extrusion granulation is carried out in a twin-screw extruder, wherein the temperature of the feeding section of the twin-screw extruder is 120-140°C, the temperature of the melt plasticizing section is 135-160°C, the temperature of the melt extrusion section is 135-150°C, and the temperature of the die section is 120-155°C; the main engine speed is 20-25rpm, and the feeding speed is 15-18rpm.
Citation Information
Patent Citations
Environmentally-friendly flame retardant for substituting antimony trioxide
CN101914217A
High-flame-retardant polyvinyl chloride cable compound and preparation method thereof
CN101942156A
Antimony-free flame-retardant polyvinyl chloride wire and cable material and preparation method thereof
CN104403224A
Environment-friendly, low-volatility and low-odor PVC (polyvinyl chloride) cable material and preparation method thereof
CN104448613A
Polyvinyl chloride (PVC) flame-retardant jacket material
CN105837998A